16-QAM Vector Terahertz-Wave Signal Generation by Simple MZM-Based Optical Frequency Comb - Kaile Li; Yuanxiang Chen; Yongtao Huang; Yitong Li; Ying Han; Jia Fu; Jianguo Yu (IEEE Photonics Journal)
A novel photonic vector THz-wave signal generation at terahertz-wave (THz-wave) band by Mach Zendell modulator (MZM) -based optical frequency comb and in-phase and quadrature (IQ) modulator for signal modulation scheme is proposed. And we demonstrate 16 quadrature-amplitude-modulation (QAM) vector THz-wave signal generation and transmission by simulation. The IQ modulator is driven by a 2-Gbaud/3-Gbaud 16-QAM-modulated baseband signal.The MZM is driven by a radio frequency signal at the frequency of 30 GHz to generate optical frequency comb. The generated 390 GHz THz-wave radio frequency signal after heterodyne beating in uni-travelling photodiode (UTC-PD) is transmitted over 0 km/10 km single-mode-fiber transmission. The 390-GHz electrical vector THz-wave signal carring 16-QAM modulation can be generated with a bit error ratio (BER) of less than the hard-decision forward-error-correction (HD-FEC) threshold of 3.8e-3. To the best of our knowledge, it's the first time to generate 390 GHz photonic vector THz-wave signal on the basis of simple MZM-based optical frequency comb.